Towards the decolonization of the extractive regime: Patterns and limits of judicialization in mining conflicts - María Ximena González-Serrano; Digno José Montalván-Zambrano; Lieselotte Viaene (Íconos)
In this article, we have been motivated by the need to address a little-studied aspect of extractivism in Latin America: the colonial foundations of the regulatory framework of corporate mining and the limits of the judicialization of human rights in order to achieve transformation. Our analysis draws on theoretical references from the field of strategic litigation, the origins of international law and decolonial studies. We used a multiscale methodology that took Guatemala and Colombia as case studies at the national level and the Inter-American System of Human Rights at the international level. At the same time, we wove an interdisciplinary dialogue between authors with different backgrounds and integrated a variety of academic sources and judicial sentences. Thus, we constructed from the most relevant sources a colonial genealogy of mining regulations and their continuity in the republican and contemporary regulations in the countries in question. In addition, we identify common patterns in the judicialization of mining conflicts at the domestic and inter-American levels and demonstrate their ineffectiveness in the modification of the regulations governing mining. We conclude with a reflection on new theoretical and methodological paths both in legal practice and in applied theoretical research, possible horizons for the decolonization of law and, in particular, mining law.